MdbHLH93, an apple activator regulating leaf senescence, is regulated by ABA and MdBT2 in antagonistic ways - An, Jian-Ping (The New phytologist, 2019)
© 2018 Shandong Agricultural University New Phytologist © 2018 New Phytologist Trust.